The Resistance to Freeze-Drying and to Storage Was Determined as the Cellular Ability to Recover Its Survival Rate and Acidification Activity - Ibourahema Coulibaly; Robin Dubois-Dauphin; Jacqueline Destain; Marie-Laure Fauconnier; Georges Lognay; Philippe Thonart (International Journal of Microbiology)
The protective effects of the fatty acid composition and membrane action of the acidification activity of two strains of Lactobacillus kept at 20∘C were studied. The addition of sorbitol, monosodium glutamate and glycerol during storage is causing the decline of acidification and increased concentrations of unsaturated fatty acids observed in both strains. The addition of sorbitol and monosodium glutamate does not alter the fatty acid composition, whatever the strain, but increases the resistance to freeze-drying of L. plantarum CWBI-B1419 and improves survival during storage. The addition of these preservatives and decreased activity of acidification improves the ratio unsaturated. These results indicate that the survival during storage and freeze-drying resistance are closely related to the composition of membrane fatty acids. This behaviour can be interpreted as an adaptation of L. plantarum B1419-CWBI supplemented by cryoprotectant additives such as sorbitol or monosodium glutamate sorbitol and monosodium glutamate as an additive. L. plantarum CWBI-B1419 presents a greater adaptation to culture conditions than L. paracasei ssp. paracasei LMG9192T.